Marine Mollusk‐Derived Agents with Antiproliferative Activity as Promising Anticancer Agents to Overcome Chemotherapy Resistance. Issue 4 (7th December 2016) - Ciavatta, Maria Letizia; Lefranc, Florence; Carbone, Marianna; Mollo, Ernesto; Gavagnin, Margherita; Betancourt, Tania; Dasari, Ramesh; Kornienko, Alexander; Kiss, Robert
Abstract: The chemical investigation of marine mollusks has led to the isolation of a wide variety of bioactive metabolites, which evolved in marine organisms as favorable adaptations to survive in different environments. Most of them are derived from food sources, but they can be also biosynthesized de novo by the mollusks themselves, or produced by symbionts. Consequently, the isolated compounds cannot be strictly considered as "chemotaxonomic markers" for the different molluscan species. However, the chemical investigation of this phylum has provided many compounds of interest as potential anticancer drugs that assume particular importance in the light of the growing literature on cancer biology and chemotherapy. The current review highlights the diversity of chemical structures, mechanisms of action, and, most importantly, the potential of mollusk‐derived metabolites as anticancer agents, including those biosynthesized by mollusks and those of dietary origin. After the discussion of dolastatins and kahalalides, compounds previously studied in clinical trials, the review covers potentially promising anticancer agents, which are grouped based on their structural type and include terpenes, steroids, peptides, polyketides and nitrogen‐containing compounds. The "promise" of a mollusk‐derived natural product as an anticancer agent is evaluated on the basis of its ability to target biological characteristics of cancer cells responsible for poor treatment outcomes. These characteristics include high antiproliferative potency against cancer cells in vitro, preferential inhibition of the proliferation of cancer cells over normal ones, mechanism of action via nonapoptotic signaling pathways, circumvention of multidrug resistance phenotype, and high activity in vivo, among others. The review also includes sections on the targeted delivery of mollusk‐derived anticancer agents and solutions to their procurement in quantity.